Policy challenges of the heterogeneity of the value of statistical life - Viscusi, W. Kip (Foundations and trends in microeconomics, 2011)
Economic research has developed estimates of the heterogeneity of the value of statistical life (VSL) on dimensions such as individual age, income, immigrant status, and the nature of the risk exposure. This paper examines the empirical evidence on the heterogeneity of VSL and explores the potential implications for the valuation of regulatory policies. Previously, the U.S. Environmental Protection Agency (EPA) unsuccessfully sought to adopt a simple age discount percentage for VSL based on survey evidence. However, labor market estimates of VSL indicate a pattern that tracks lifetime consumption trajectories, as the VSL rises with age and eventually tapers off but does not plummet with age.